Acute kidney injury in the fetus and neonate. Issue 2 (April 2017) - Nada, Arwa; Bonachea, Elizabeth M.; Askenazi, David J.
Abstract: Acute kidney injury (AKI) is an under-recognized morbidity of neonates; the incidence remains unclear due to the absence of a unified definition of AKI in this population and because previous studies have varied greatly in screening for AKI with serum creatinine and urine output assessments. Premature infants may be born with less than half of the nephrons compared with term neonates, predisposing them to chronic kidney disease (CKD) early on in life and as they age. AKI can also lead to CKD, and premature infants with AKI may be at very high risk for long-term kidney problems. AKI in neonates is often multifactorial and may result from prenatal, perinatal, or postnatal insults as well as any combination thereof. This review focuses on the causes of AKI, the importance of early detection, the management of AKI in neonates, and long-term sequela of AKI in neonates.